Soil fertility of rice- blackgram cropping sequence as influenced by different organic sources of nutrients (Bangladesh Journal of Botany, 2022)
Residual effects of organic manures on rice-blackgram cropping sequence, during 2017 and 2018 at Thoppur, Thirupparankundram, Madurai were studied at field levels. Twelve treatment combinations comprising various sources of nutrients (Green manure @ 6.25 t/ha, neem cake@250 kg/ha, Enriched FYM @1.0 t/ha, tamarind seed powder @ 100 kg/ha, vermicompost @ 4 t/ha, Panchagavya @ 3%, Multi varietal seed technique, herbal pest repellant spray @ 10%, state recommendation) in a Randomized Block Design with three replications laid out for rice, were used for rice fallow blackgram. The mean soil available N (345 kg/ha), phosphorous (33 kg ha-1) and potassium (310 kg/ha) of 2 cropping cycles were significantly superior with the application of green manure @ 6.25 t/ha along with split application of vermicompost in four equal splits @ 4 t/ha as basal, at active tillering, panicle initiation and flowering stages + Panchagavya @ 3 per cent as foliar spray twice at active tillering and panicle initiation stages. A similar trend was also observed with respect to soil chemical and biological properties viz., soil pH, organic carbon, fungi, bacteria and actinomycetes population in the same treatment. The results of present study confirm the benefits of organic sources of manures on the nutrient retention characteristic of soil and will be conducive to improve the soil fertility for achieving sustainable soil health.Bangladesh J. Bot. 51(2): 289-296, 2022 (June)